Mapping partition: Politics, territory and the end of empire in India and Pakistan - Fitzpatrick, Hannah (Hoboken, USA: Wiley, 2024)
"Mapping Partition delivers the first in-depth geographical account of the partition of India and Pakistan in 1947. The book explores the impact of colonial geography and geographers on the boundary, both during the partition process and in the period preceding it. Drawing on extensive archival research, Hannah Fitzpatrick argues that colonial geographical knowledge underpinned the partition process in heretofore unacknowledged ways. The author also discusses the consequences of placing different ethnic, communal, and linguistic groups onto the colonial map and the growing importance of majority and minority populations in representative democratic politics. Mapping Partition: Politics, Territory and the End of Empire in India and Pakistan is required reading for students and researchers studying geography, colonial and imperial history, South Asian studies, and interdisciplinary border studies"--
Remapping partition -- Surveying and boundary-making in Colonial India -- Territorialising India and Pakistan -- Geographies of the Punjab Boundary Commission -- Oskar Spate, the Muslim League and geographical expertise -- Partition to partitions: new avenues for historical geography.
Includes index.
Keywords: Cartography -- India -- History -- 20th century; Partition; Cartography -- Pakistan -- History -- 20th century; Partition, Territorial; Historical geography; India -- Politics and government -- History -- 20th century; Pakistan -- Politics and government -- History -- 20th century